THE EFFECT OF GREEN BANKING, CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY ON COMPANY VALUE IN THE BANKING SECTOR LISTED ON THE IDX - Soqia Salsabila; Darmawati Muchtar; Rico Nur Ilham; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze the effect of Green Banking, Corporate Social Responsibility (CSR), and profitability on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Firm value is proxied by Price to Book Value (PBV). The independent variables used are Green Banking (X1), CSR (X2), and profitability measured by Return on Assets (ROA) (X3). This research employs a quantitative method using secondary data obtained from the annual reports and sustainability reports of banks listed on the IDX. The sample was selected using a purposive sampling method, resulting in 37 companies with a total of 148 observations. Data analysis was conducted with the aid of EViews software through panel data regression. The best model was determined using the Chow test and Hausman test. The results show that Green Banking has no effect on firm value. CSR has a negative and significant effect on firm value. Profitability (ROA) has a negative and significant effect on firm value.